Materiality of TEI Encoding and Decoding: An Analysis of the Western European Union Archives on Armament Policy - Florentina Armaselu; Verónica Martins; Catherine Emma Jones (Journal of the Text Encoding Initiative)
By combining traditional historical enquiry with TEI XML encoding and decoding in a corpus analysis phase, the project aims at addressing research questions mainly related to the French and British positions on the topics of armament design and production and of armament control within the Western European Union (WEU) from 1954 to 1982. The paper focuses on the annotation of speakers (different countries and institutional representatives) and their discourse in a selection of institutional documents (minutes, notes, studies, memoranda) (encoding phase) and the identification of linguistic patterns on armament issues in their discourse, as well as the interpretation of results (decoding phase). From a larger perspective, the study considers the TEI encoding as adding to the original text a “material” layer that further supports both machine and human interpretation (decoding). In this sense, this study may move closer to the concept of “material hermeneutics,” by understanding code, and digital technology in general, as an instrument we can use in hermeneutic ways to produce knowledge.